The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1124/jpet.109.150961
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Induces Expression of C-Reactive Protein in Human Blood Vessels

Abstract: C-reactive protein (CRP) is a powerful independent risk factor for cardiovascular diseases. Elevated mechanical strain on vessels induces the local expression of proinflammatory cytokines. We hypothesized that mechanical strain on vessels may induce local CRP expression. Human saphenous vein and internal mammary artery (IMA) rings were stretched in vitro with a mechanical strength of 1, 3, or 5 g. Reverse transcriptionpolymerase chain reaction and enzyme-linked immunosorbent assay results showed that mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…In addition, integrin-dependent MAPKs (ERK1/2) activation mechanism involves Rho GTPase (RhoA, Rac1) [72,76,77]. Ultimately, integrin-dependent MAPKs pathway mechanically leads to activation of transcription factor NF-kB and p53 [72,76,77]. Thereby, integrin MAPK signalling pathway is a critical signal pathway for SMC proliferation and apoptosis under mechanical stimulation.…”
Section: Co-culture Model Under a Haemodynamic Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, integrin-dependent MAPKs (ERK1/2) activation mechanism involves Rho GTPase (RhoA, Rac1) [72,76,77]. Ultimately, integrin-dependent MAPKs pathway mechanically leads to activation of transcription factor NF-kB and p53 [72,76,77]. Thereby, integrin MAPK signalling pathway is a critical signal pathway for SMC proliferation and apoptosis under mechanical stimulation.…”
Section: Co-culture Model Under a Haemodynamic Environmentmentioning
confidence: 99%
“…Activated integrins also can lead to integrin-dependent activation of MAPKs via FAK through integrin-dependent Src-Ras-MEK1/2 activation [63]. In addition, integrin-dependent MAPKs (ERK1/2) activation mechanism involves Rho GTPase (RhoA, Rac1) [72,76,77]. Ultimately, integrin-dependent MAPKs pathway mechanically leads to activation of transcription factor NF-kB and p53 [72,76,77].…”
Section: Co-culture Model Under a Haemodynamic Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Stretch increases the expression of C-reactive protein (CRP) mRNA and protein in saphenous vein and internal mammary artery rings exposed to stretch [78]. CRP is a nonspecific marker of inflammation and is considered an independent risk factor for atherosclerosis and atherosclerosis-related diseases [79,80].…”
Section: Stretch-regulated Genes Affecting the Inflammatory Response mentioning
confidence: 99%
“…Previous studies have demonstrated that CRP expression is induced under mechanical strain, which in turns activates stretch-activated channels (SACs) in the absence of an inflammatory reaction in case of rabbit and human vessel rings and models [16,17]. Clearly, CRP does not function solely as an inflammatory factor.…”
Section: Introductionmentioning
confidence: 99%